(untitled) (Journal of Pharmaceutical Negative Results, 2022)
During severe liver damages, xanthine oxidase (XO) released into the blood, so a blood assay for XO is a way to determine if liver damage has happened.In this work we aimed to determinelevels of XO in serum of healthy and hepatitis B subjects using an enzyme linked immunosorbent assay ELISA. In the first step, we purified XO from frozen human milk, then we assessed the purity of the enzyme through, SDS-PAGE and UV-visible spectrum. Then, we used this enzyme to immunize rabbits to get anti XO antibodies. After that, we optimized a sensitive sandwich ELISA test to determine levels of XO in serum of normal and hepatitis B subjects. After purification, the yield of XO enzyme was 5.7 ± 1.8 mg /L (n=4). Anti-XO antibodies were purified with affinity chromatography on XOR immobilized column. The obtained antibodies were from IgG class. The developed sandwich ELISA test allowed us to get a XOR levels of 5.11±1.23 ng/ml for healthy subjects and 45.15±15.61 ng/ml for hepatitis B patients. These results showed no significant correlation between XO level and transaminases. Based on the obtained results, the level of XO in serum of hepatitis B subject is significantly higher than its level in normal subjects.